Management of Movable Assets as Endowment According to Law no. 41 of 2004 Concerning Endowment (Case Study: Al-Ikhlas Mosque Ambulance, Hinai Village) - Humairah, Fanny Azelita; Nasution, Abdul Halim (LEGAL BRIEF, 2025)
Endowment is action wakif law for separate or deliver part treasure object his For utilized forever or in term time certain in accordance its importance for religious purposes and/ or welfare general according to sharia. Research This discuss draft endowment object move according to Law No. 41 of 2004, management endowment object moving at the Al-Ikhlas Hinai Mosque, as well implementation Constitution the to management waqf ambulance car . Research This aiming know How endowment object move managed and to what extent the implementation of Law No. 41 of 2004 is applied . Research use method juridical-empirical with emphasize principle certainty law and welfare , and data obtained through observation and interview . The results show that management The ambulance waqf was carried out by BKM Al-Ikhlas Mosque and utilized For Hinai community and its surroundings . However , its utilization Still nature consumptive and not yet productive . In addition , the ambulance has not registered with the Indonesian Waqf Board (BWI) because BKM's ignorance regarding procedure registration , so that No in accordance with provisions of Article 32 of Law No. 41 of 2004 concerning obligation registration endowment object move.